Theoretical Review of the Relationship between Internal and External Support and Addiction Online Games for Children - Damayanti, Dari; Bahar, Meify; Sovitriana, Rilla (Causalita, 2025)
The advent of information and communication technology has significantly changed children's daily lives, with 84.71% of students accessing the internet. While urban areas show higher rates of internet usage (89.47%) compared to rural areas (77.78%), mobile phones dominate as the primary means of internet access. This increased connectivity has resulted in the growing popularity of gaming, which, while entertaining, is associated with negative impacts such as addiction, mental disorders, and decreased physical health and academic performance. Studies show that almost all early adolescents play game online daily, with approximately 7% playing for more than 30 hours per week, raising concerns about their well-being. Two key factors influencing addiction include self-esteem and emotional regulation; children with low self-esteem are more likely to seek validation through gaming. Effective stress management is also crucial in combating addictive behavior, as children experiencing stress are more susceptible to gaming addiction. Support systems play a crucial role in mitigating these challenges, encompassing internal mechanisms such as self-esteem and emotional resilience, as well as external influences from family, peers, and the educational environment. Families can set limits and provide alternatives to gaming, while schools can educate and implement policies to prevent addiction. Collaborative and supportive relationships, both at home and at school, can help children maintain a healthier balance with technology, ensuring that dare games serve as entertainment and not a harmful addiction. Collectively addressing these issues can provide valuable insights for practitioners, parents, and educators in developing effective interventions for children at risk of dare game addiction